Evidence of the octupole correlation between the shears bands in 142 Eu - Ali, Sajad; Rajbanshi, S.; Raut, R.; Pai, H.; Wang, Y.Y.; Gangopadhyay, G.; Meng, J.; Palit, R.; Nag, Somnath; Biso, Abhijit; Saha, S.; Sethi, J.; et al. (Elsevier B.V., 2019)
Two opposite parity dipole sequences (DB I and DB II) in 142Eu have been investigated using the Indian National Gamma Array (INGA), and heavy-ion induced fusion-evaporation reaction, 116Cd(31P, 5n) at ELab = 148 MeV. The Configurations of these bands are assigned on the basis of tilted axis cranking covariant density functional theory (TAC-CDFT) calculations. The measured B(M1) and B(E2) rates of the DB I and DB II, have been well reproduced within the shears mechanism with the principal axis cranking model (SPAC) calculations leading to the conclusion that these bands have been based on the shears mechanism. The large B(E1) transition rates between DB I and DB II indicate the existence of octupole correlation in 142Eu that has also been corroborated through microscopic multidimensionally-constrained covariant density functional theory (MDC-CDFT) calculations. Thus, the present investigation leads to the novel observation of the presence of octupole correlation between two shears band. © 2019 The Author(s)
Keywords: Lifetime measurement; Octupole correlation; Principal axis rotation; Tilted axis rotation